Experimental Study of Wave Attenuation Across an Artificial Salt Marsh - Baker, Scott; Murphy, Enda; Cornett, Andrew; Knox, Paul (Frontiers in Built Environment, 2022)
Scaled laboratory experiments were conducted to investigate the effectiveness of marsh vegetation in dissipating wave energy and reducing wave overtopping discharges at the crest of a dyke located immediately landward of the marsh. Model dyke and marsh platform features, loosely based on archetypes found in Atlantic Canada, were constructed in a wave basin at 1:20 scale and exposed to a broad range of waves and water level conditions. The 2D experiments were conducted using idealized surrogate vegetation (both rigid and flexible), and the model setup featured four parallel flumes which enabled four alternative configurations to be investigated simultaneously. The experiments investigated the sensitivity of wave attenuation and overtopping to the length of the vegetation field, vegetation characteristics (stem density, height, and flexibility) and varying water levels and wave conditions. The study outputs have helped to address knowledge gaps and provide evidence to support and inform broader use of hybrid marsh-dyke systems and managed dyke realignment to help manage flood and erosion risk and improve coastal resilience in Canada.